Microbial communities on eelgrass (Zostera marina) thriving in Tokyo Bay and the possible source of leaf-attached microbes - Iqbal, Md Mehedi; Nishimura, Masahiko; Haider, Md. Nurul; Yoshizawa, Susumu (Frontiers in Microbiology, 2023)
Zostera marina (eelgrass) is classified as one of the marine angiosperms and is widely distributed throughout much of the Northern Hemisphere. The present study investigated the microbial community structure and diversity of Z. marina growing in Futtsu bathing water, Chiba prefecture, Japan. The purpose of this study was to provide new insight into the diversity of microbial communities of leaves of different ages, the root-rhizome of Z. marina, and the surrounding microenvironments (suspended particles, seawater, and sediment). The microbial composition of each sample was analysed using 16S ribosomal gene amplicon sequencing. Each sample type was found to have a unique microbial community structure. Leaf-attached microbes changed in their composition depending on the relative age of the eelgrass leaf. Special attention was given to a potential microbial source of leaf-attached microbes. Microbial communities of marine particles looked more like those of eelgrass leaves than those of water samples. It was observed in this experiment that leaf-attached microbes were derived from suspended particles, which could allow them to go back and forth between eelgrass leaves and the water column.